Efeito da telerreabilitação sobre a capacidade funcional do exercício, função pulmonar, aptidão física, dispneia, fadiga e qualidade de vida em pacientes com covid-19 : uma revisão sistemática e metanálise - Martins, Renata de Lima (2023)
Introduction: COVID-19 can cause systemic problems and complications in various organs and system, leaving sequelae in those affected. In order to treat the functions impaired by COVID-19, physical rehabilitation has set out to restore or minimize the damage caused by the disease. Rehabilitation via digital resources or telerehabilitation is indicated as a branch of telehealth that characterizes a remote rehabilitation control system through telecommunication technologies, which has proven to be effective, saving time and resources for health care. Objective: Identify the effects of telerehabilitation on functional capacity, lung function, dyspnea, fatigue and quality of life in patients affected by COVID-19. Methods: This study was registered in the PROSPERO systematic review protocol database with registration CRD42022347642 The PICO strategy used the following inclusion criteria: people of both sexes, aged ≥ 18 years with and after COVID-19, hospitalized or not, who were undergoing telerehabilitation protocols compared or not to in-person treatments or usual care. The outcomes assessed were functional capacity, lung function, respiratory muscle strength, physical fitness parameters, quality of life, dyspnea and fatigue. The search was carried out on the following databases: PubMed/MEDLINE, Cochrane Library, PEDro Physiotherapy Evidence Database, CINAHL Database/EBSCO and Web of Science. Books, meta-analyses, reviews and systematic reviews were excluded. The quality and reporting of the studies were analyzed using the TESTEX scale. Quantitative synthesis was carried out in Review Manager (RevMan 5.4) with analyses to measure the standardized mean difference (SMD) or mean difference (MD) between trials, with 95% confidence intervals (95% CI). Heterogeneity was assessed by I2, and random or fixed effects were applied according to the heterogeneity of the study. Results: Thirty-four articles evaluating 1,344 individuals with and after COVID-19 were included for the qualitative synthesis, and fourteen studies went on to the meta-analysis. The data revealed that telerehabilitation improved functional capacity (MD 90.09 [64.12, 116.06m] I2 = 52%, P < 0.00001), agility [MD -0.69 [95%CI -1.33, -0. 04], I2 = 0%, P < 0.04], lower limb strength and endurance [DMP 0.74 [95%CI 0.52, 0.96Kg], I2 = 10%, P < 0.00001], FEV1 [MD 0.20 [95%CI 0.04, 0.37L], I2 = 55%, P = 0.02], and dyspnea [DMP -0.94 [95%CI -1.64, -0.24], I2 = 90%, P = 0.009]. It was also found that telerehabilitation improved inspiratory muscle strength [MD 13.71 [95%CI 5.41, 22.00cmH2O], I2 = 0%, P = 0.001] but was not favorable for improving lung function. In the subgroup analysis, the telerehabilitation protocols with RMT associated or not with other physical modalities were favorable for increasing handgrip strength [MD 4.69 [95%CI 0.44, 8.94kg], I2 = 0%, P = 0.03] and fatigue [MPD -0.97 [95%CI -1.74, -0.20], I2 = 74%, P = 0.01], P < 0.00001]. On the other hand, quality of life improved with the offer of telerehabilitation during the COVID-19 contagion phase. Conclusion: Telerehabilitation is favorable for improving functional capacity, inspiratory muscle strength, lower limb aerobic strength and endurance, agility and dyspnea. The subgroup analysis showed a reduction in fatigue, an improvement in handgrip strength and FEV1 in the protocols with MDRT alone or combined with other exercise modalities. Quality of life was improved in the protocols used in the contagious phase of the disease and the improvement in functional capacity was independent of the time and type of intervention carried out.